Respuesta :

leena

Answer:

[tex]y = \frac{-1}{2}(x-3)[/tex]

Step-by-step explanation:

To determine the inverse of an equation, simply switch the places of the 'x' and 'y' variables. Therefore:

f(x) = -2x + 3

Use 'y' in place of f(x).

y = -2x + 3

Switch the 'x' and the 'y':

x = -2y + 3

Subtract '3' from both sides:

x - 3 = -2y

Divide both sides by '-2':

[tex]y= \frac{x-3}{-2}[/tex]

Simplify:

[tex]y = \frac{-1}{2}(x-3)[/tex]

Answer:

The correct answer is D

Step-by-step explanation:

Trust

ACCESS MORE